The legal framework and the role of the state in protecting undocumented immigrants against forced eviction in South Africa - Nshimbi, Christopher Changwe (University of Pretoria, 2024)
Mini Dissertation (LLM (Multidisciplinary Human Rights))--University of Pretoria, 2024.